Legal Protection for Farmers through Farming Business Insurance as a form of Risk Mitigation Welfare State - Hesti Dwi Astuti; Neni Sri Imaniyati; Husni Syawali; Neni Ruhaeni (Journal La Sociale, 2022)
Agricultural business activities are businesses that have a high risk of uncertainty. Global climate change has an impact on agricultural products resulting in decreased income and welfare of farmers, so that legal protection is needed by the government as an effort to protect farmers. The research method uses descriptive qualitative analytical techniques, in which this study describes and analyzes systematically, factually, and accurately about Legal Protection for Farmers Through Agricultural Insurance Agricultural premium subsidy insurance is a form of legal protection for farmers who have the aim of protecting against crop failures that is a form of risk mitigation as a form of mitigation Risk Welfare State.